2015
DOI: 10.7150/thno.8387
|View full text |Cite
|
Sign up to set email alerts
|

Parthenolide Inhibits Cancer Stem-Like Side Population of Nasopharyngeal Carcinoma Cells via Suppression of the NF-κB/COX-2 Pathway

Abstract: Cancer stem cells play a central role in the pathogenesis of nasopharyngeal carcinoma and contribute to both disease initiation and relapse. In this study, cyclooxygenase-2 (COX-2) was found to regulate cancer stem-like side population cells of nasopharyngeal carcinoma cells and enhance cancer stem-like cells' characteristics such as higher colony formation efficiency and overexpression of stemness-associated genes. The regulatory effect of COX-2 on cancer stem-like characteristics may be mediated by ABCG2. CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 52 publications
4
47
0
Order By: Relevance
“…59 Briefly, using the DNA Transfection Reagent X-tremeGENE HP (Roche), the lentiviral vectors described above, and viral packaging plasmids (pCMV-delta 8.9 and VSVG), were co-transfected into HEK293T cells to produce lentiviral stocks. HEK cells were infected with lentivirus carrying pLKO- PTGS2 -shRNA recombinant plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…59 Briefly, using the DNA Transfection Reagent X-tremeGENE HP (Roche), the lentiviral vectors described above, and viral packaging plasmids (pCMV-delta 8.9 and VSVG), were co-transfected into HEK293T cells to produce lentiviral stocks. HEK cells were infected with lentivirus carrying pLKO- PTGS2 -shRNA recombinant plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…A functional marker of CSCs is the ability to grow as spheroid colonies in defined serum-free culture conditions that supports the proliferation of undifferentiated cells [85]. Cells that overexpress COX-2 exhibit greater sphere forming efficiency and clonogenicity than those that express low levels of COX-2 [75, 86, 87]. In breast CSCs, isolated from the primary tumours of HER2/Neu transgenic mice, COX-2 expression was upregulated 30-fold in CSCs compared to non-CSCs, and constituted part of an eight-gene signature that correlated with breast cancer patient survival [88].…”
Section: Cox-2 Plays a Central Role In Cancermentioning
confidence: 99%
“…PTL inhibited histamine release from rat peritoneal mast cells [26]. Further studies revealed that it inhibits inflammatory mediators including activity and expression of cyclo-oxygenase (COX) specifically COX-2, which also enhances cancer stem-like cells' characteristics such as higher colony formation efficiency and over expression of stemness-associated genes [27][28][29]. The compound was found to inhibit activation of transcription factor NFκB by both at the transcriptional level and by direct inhibition of associated kinases (IKK-β) [30,31].…”
Section: Parthenolide and Statmentioning
confidence: 99%
“…References Cell Proliferation/ Apoptosis associated Molecules References NFκB [14], [30], [31], [35], [43], [48], [90] NFκB [17], [18], [21], [52], [54], [64], [78][79], [90] IKK-β [30][31][32], [48] [ERK/MEK/MAPK/ELK1] [14], [37], [48], [51] iNOS [39] β1-arrestin, Csk, FAK, FGFR2, PKC [51] STAT1/STAT3 [36], [51], [83][84][85][86][87][88] STAT1/STAT3 [36], [51], [55][56], [83][84][85][86][87][88] Cyclooxygenase (COX) [27][28][29], [37] JNK [42], [43], …”
Section: Inflammatory Moleculesmentioning
confidence: 99%